Calculation of Aggregate Accident Claims Based on the Number and Magnitude of Accident Losses in Indonesia from 2013 to 2022 - Siahaan, Roy Donald Pangeran (Research Collaboration Community (RCC), 2025)
Accident losses are unavoidable when accidents occur. Data from the Indonesian Central Bureau of Statistics (BPS) show an increasing trend in accident claim amounts in recent years. This study aims to calculate aggregate accident claims based on the number and magnitude of accident losses in Indonesia from 2013 to 2022, enabling insurance companies or entities covering such losses to estimate the total liability required for all accident claims. The Generalized Extreme Value (GEV) distribution was applied to model claim amounts, while the negative binomial distribution was used for the number of accidents. The results show that the expected value of aggregate claims is IDR 236,768,463,076.93, with a variance of 7.28 × 10²⁰. The findings indicate that these distributions are suitable for modeling aggregate claims, providing insights for determining appropriate insurance premiums.